National transformation success @ A theory of everything based on simplicity and sophistication - Han, Chun Kwong (Research Management Institute, Universiti Teknologi MARA, 2013)
The Government has been taking a radically new approach to national transformation in the past three years. The Government Transformation Programme was initiated in 2009, followed by the New Economic Model and Economic Transformation Programme in 2010, and subsequently political and rural transformation. The “Transformation Budget 2012” announced the “National Transformation Policy”. Presently, transformation can be perceived as the inception stage, as the various programmes will be undergoing a long continuous implementation journey into 2020. In order to make a real significant change to the country, the transformation needs to be driven from a synthesis of economic, managerial, organizational, social and technological dimensions at the multiple levels of the individual, organization, industry, government, society and nation. We offer another way of seeing and doing transformation using an enhanced critical theory and critical practice. We define critical practice as an iterative reflexive process, firstly by developing knowledge-for-understanding from a sophisticated model of reality. Secondly, we provide a critique of underpinning assumptions and presumptions whereby the constraining conditions of the status quo and emancipation become knowable and explicit, that is, knowledge-for-evaluation. Thirdly, we re-create, re-define, re-design, re-imagine, re-invent and re-vision the pragmatic, doable and implementable programmes from knowledge-for-action. Finally, we combine the extant government transformation model of “Doing and Being”, a simplicity model with critical practice, which is a model of sophistication. This new ‘theory of everything’ could be the underlying basis of the transformation methodology for the success of the various national transformation programmes to convert Malaysia into a high-income developed country by 2020.